2016
DOI: 10.5851/kosfa.2016.36.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidative and Anti-Inflammation Activities of Pork Extracts

Abstract: This study was conducted to evaluate the antioxidative and anti-inflammatory effects of boiled pork powder (BPP) and hot water extract powder (HWEP) from 4 cuts of meat from Landrace × Yorkshire × Duroc (LYD). The highest DPPH radical scavenging activities determined were from BPP of Boston butt (13.65 M TE) and HWEP of loin (19.40 M TE) and ham (21.45 M TE). The 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging activities of BPP from shoulder ham (39.28 M TE) and ham (39.43 M TE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…With an increase in storage time, antioxidant activities (DPPH and ABTS radical scavenging activities, FRAP activity) of loin meat from both groups decreased (p<0.05; Table 8 ), similar to the results of Kim and Jang (2021) . Previously, the DPPH, FRAP, and ABTS activities of boiled pork were determined to be 10.58–13.65, 3.66–5.31, and 26.60–39.43 μmol TE/g dry matter, respectively ( Gil et al, 2016 ), while the ABTS and FRAP activities of black goat loin were obtained as 12.90 and 15.92 μmol TE/g dry matter, respectively ( Kim et al, 2019 ). These results imply that loin meat from the KLA group had higher ABTS radical scavenging activity than boiled pork and black goat meat, similar to beef loin.…”
Section: Resultsmentioning
confidence: 99%
“…With an increase in storage time, antioxidant activities (DPPH and ABTS radical scavenging activities, FRAP activity) of loin meat from both groups decreased (p<0.05; Table 8 ), similar to the results of Kim and Jang (2021) . Previously, the DPPH, FRAP, and ABTS activities of boiled pork were determined to be 10.58–13.65, 3.66–5.31, and 26.60–39.43 μmol TE/g dry matter, respectively ( Gil et al, 2016 ), while the ABTS and FRAP activities of black goat loin were obtained as 12.90 and 15.92 μmol TE/g dry matter, respectively ( Kim et al, 2019 ). These results imply that loin meat from the KLA group had higher ABTS radical scavenging activity than boiled pork and black goat meat, similar to beef loin.…”
Section: Resultsmentioning
confidence: 99%
“…Mirzaei et al [29] have reported that goat meat had 42% diphenyl-picrylhydrazyl radical-scavenging activity. In our previous study, boiled pork meat showed a FRAP activity of 3.66 to 5.31 μmol TE/g DM, ABTS activity of 26.60 to 39.43 μmol TE/g DM, and an ORAC activity of 143.74 to 198.35 μmol TE/g DM [30]. Hanwoo beef showed an ORAC activity of 145.54 μmol TE/g DM [31].…”
Section: Resultsmentioning
confidence: 99%
“…However, BGR had higher collagen and mineral contents, especially with respect to the Ca/P ratio, than did BGL. Although there was no significant difference in the antioxidant activity between BGL and BGR, both goat meat cuts showed a higher reducing power activity than did boiled pork meat [30] assessed in previous studies. This work was a novel study comparing nutritional values and antioxidant activities of black goat meat with respect to the cut.…”
Section: Resultsmentioning
confidence: 99%
“…Foot diameter was determined in all animals at time 0 (before injection) and after 1, 2, 3, and 4 h after the injection. This process was performed following the process previously described [ 40 ].…”
Section: Methodsmentioning
confidence: 99%